PRÁTICA DE RESPONSABILIDADE SOCIAL EMPRESARIAL PARA A INTEGRAÇÃO DA COMUNIDADE: ESTUDO DE CASO UNIDADE DE POLÍCIA PACIFICADORA PROVIDÊNCIA - Santos, Wellington Oscar dos (2013)
The objective of this research is to analyze the importance of Corporate Social Responsibility for the company, society and the state through the experience of IESA Oil & Gas company, in the constitution of the Social Responsibility Department, working in partnership with the state, and especially demonstrating their reflections, the return to stakeholders. The research is guiding question: is it possible to integrate and socialize the community through public-private partnership, combining into one Pacifying Police Unit (UPP)? To answer this question books and articles on the subject object of this study were analyzed. In addition, questionnaires to 30 residents of the community of Providence were applied to identify the perception of ourselves in relation to courses provided by the partnership between IESA and FIRJAN. It was concluded that it is feasible to public - private partnership with the community to socialize intuited and students taking courses realized mostly a lifestyle change for the better.